Beyond the ice : Creswell Crags and its place in a wider European context - Beresford, Matthew (Archaeopress, 2012)
Since the discovery of Britain's first Ice Age cave art in 2003, the site of Creswell Crags has gained international recognition as one of Britain's leading Ice Age sites. For the first time the history of the site is brought together in one accessible volume. Documenting the early fieldwork at the site it uncovers antiquarian discoveries such as the famous horse engraving, excavations in the 1920s that saw our understanding of our early ancestors take shape, discusses the demise of the Neanderthals and the emergence of Modern Man, and looks at how Creswell Crags grew as a heritage attraction of potential World Heritage Status.